(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The purpose of this research is to produce an android-based application through an ethnomathematical approach for the scope of three-dimensional geometry material that is feasible and according to the needs of vocational students. Development research using the ADDIE model was chosen to achieve this goal, with five stages, namely analyze, design, development, implement, and evaluate. The instruments that accompany this research are the material expert and media expert validation questionnaire sheet, and the vocational school mathematics teacher response questionnaire. The results of the validation of the developed learning media obtained an expert validation value of 77.3% categorized as feasible, the teacher response value of 76% categorized as feasible. This learning media as a whole can be well received by vocational school teachers and strengthened by the validation results from experts who stated that the application was suitable for use in learning